Clarifying Leadership: High-impact Leaders in a Time of Leadership Crisis - Franco GANDOLFI; Seth STONE (Revista de Management Comparat International, 2016)
Leadership has become an increasingly difficult, complex, and multi-faceted topic in today's globalized world. New questions and challenges continue to emerge with regard to the most effective style of leading organizations and people through the 21st Century. While leadership may be seen as one of the most over-researched topics, it remains one of the most misunderstood business phenomena of our time. This conceptual research paper addresses various leadership definitions, presents an operational definition of leadership based on five criteria, categorizes and showcases some of the known attributes of highly effective leaders, and builds a case for servant leadership. The paper posits that, despite a myriad of available leadership styles and methods that have emerged, servant leadership, a philosophical position based upon the leader serving first, may have the capacity to generate positive outcomes for all stakeholders involved.